Factores asociados a la automedicación con antibióticos en adultos del distrito de Cabanilla - Puno, 2022 - Quispe Mayta, María Magdalina; Quipe Apaza , Blanca Miriam (Universidad Privada de Huancayo Franklin Roosevelt, 2023)
El objetivo es determinar el nivel de conocimiento sobre la automedicación con antibióticos en adultos del distrito de Cabanilla – Puno, 2022. Se empleó una metodología con enfoque cuantitativo, diseño no experimental, de corte transversal o transeccional y nivel causal explicativo, la muestra fue de 359 personas. Los resultados obtenidos muestran que el 56.55% de la población del distrito de Cabanilla son de sexo femenino, el 42.62% tienen unión libre, el 39.55% tienen nivel de secundario, el 25.63% superior incompleta, el 32.59% son empleados privados, el 45.40% tienen familias constituidas por 4 a 6 personas. Las conclusiones más relevantes son los conocimientos sobre automedicación con antibióticos es muy deficiente y los conocimientos sobre la resistencia antibacteriana en adultos del distrito de Cabanilla – Puno es relativamente alta.

The objective is to determine the level of knowledge about self-medication with antibiotics in adults in the district of Cabanilla - Puno, 2022. A methodology with a quantitative approach, non-experimental design, cross-sectional or transectional and causal explanatory level was used, the sample was 359 people. The results obtained show that 56.55% of the population of the district of Cabanilla are female, 42.62% have a free union, 39.55% have secondary school level, 25.63% have incomplete higher education, 32.59% are private employees, 45.40% have families consisting of 4 to 6 people. The most relevant conclusions are that knowledge about self-medication with antibiotics is very deficient and knowledge about antibacterial resistance in adults in the district of Cabanilla - Puno is relatively high.
Associated factorsto self-medication with antibiotics in adults from the district of Cabanilla -Puno, 2022
Keywords: Automedicación; Antibiótico; Factores asociados; http://purl.org/pe-repo/ocde/ford#3.01.05